2017
DOI: 10.1108/jfp-12-2015-0053
|View full text |Cite
|
Sign up to set email alerts
|

Embedding psychological thinking: an evaluation of a regional training model for probation staff

Abstract: Purpose The purpose of this paper is to outline the qualitative evaluation of a training package delivered to offender managers (OMs) working to support the implementation of the national Offender Personality Disorder (OPD) pathway and to examine qualitative changes in the way participants approach case material pre- and post-training. Design/methodology/approach In total, 21 pre- and 21 post-training responses to a case vignette were recorded and used in the analysis. OMs were asked what they would like to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The majority of these findings were positive (Brown et al, 2018;Mapplebeck et al, 2017;Radcliffe et al, 2018), suggesting that training over several days, possibly with a subsequent period of application, can improve the FCF skills of OMs. This may resolve some of the concerns raised within the opinion research described earlier (Brown & Völlm, 2013;Völlm, 2014).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The majority of these findings were positive (Brown et al, 2018;Mapplebeck et al, 2017;Radcliffe et al, 2018), suggesting that training over several days, possibly with a subsequent period of application, can improve the FCF skills of OMs. This may resolve some of the concerns raised within the opinion research described earlier (Brown & Völlm, 2013;Völlm, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Four of the identified studies aimed to understand whether the FCF skills of OMs working within the OPDP could be improved through training. Two of these studies (Brown, Beeley, Patel, & Völlm, 2018;Mapplebeck, Ramsden, Lowton, Short, & Burn, 2017) did this by assessing OM formulation skills both before and immediately after training. Minoudis et al (2013) instead assessed OM formulation skills before and after they had attended both a period of training and a number of formulation-focused consultation meetings in practice.…”
Section: Forensic Case Formulation Training (4 Studies)mentioning
confidence: 99%
See 2 more Smart Citations
“…Research following the implementation of the OPD pathway has demonstrated a beneficial impact for both probation service staff and service users, however, this has mainly focused on consultation, training and formulation, rather than the impact specifically of reflective practice (Brown et al, 2018; Clark and Chuan, 2016; Davies and O’Meara, 2018; Mapplebeck et al, 2017; McMullan et al, 2014; Ramsden et al, 2014; Shaw et al, 2012). This study aims to explore NPS and NHS staff experience and perception of reflective practice sessions, in the North and South of Tyne clusters and to consider the future allocation of resources within the OPD pathway in this area.…”
Section: Introductionmentioning
confidence: 99%